Preparation of self-gelling styptic powder based on multiple non-covalent interaction
By mixing the (methyl-based) multi-based (methyl) acrylic mono and duetthide chitin or ε-polylerate, and the free radical polymerization reaction is performed by a mix of mixing the base and the diameter. The non -common price -based self -gel hemostatic powder solves the problem of insufficient adhesion limitations and the ability to deal with complex bleeding, and realizes excellent adhesion, antibacterial and promoting healing effects.
Patent Information
- Application Number
- CN202411491344.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Traditional hemostasis methods have limitations in adhesion and insufficient ability to handle bleeding of irregular shapes, uncompressible internal organs and high-pressure arteries, and commercial hemostasis powder cannot tightly seal the wound, increasing the risk of major bleeding.
By mixing the (methyl) acrylic monomer with daily ammonium or ε-polylexine, the two-key polymerization reactions are mixed with daily ammonium chitosan or ε-polylerate. Preparation of gel, and then self -gel hemostatic powder was obtained through frozen drying and grinding. This material achieves rapid gelization and hemostasis through multiple non -covalent effects.
Self -gel hemostatic powder shows excellent adhesion performance, antibacterial properties, and the effect of promoting wound healing. It can quickly and effectively stop bleeding. It is suitable for complex conditions such as irregular shapes and high -pressure arterial hemorrhage.
Smart Images

Figure CN119367583A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of gel materials, and in particular relates to a method for preparing self-gel hemostatic powder based on multiple non-covalent effects. Background Art
[0002] In recent years, severe trauma has become a major challenge in the field of global public health, and the management of post-traumatic bleeding continues to test healthcare systems around the world. Traditional hemostatic methods are widely used, but they have obvious defects. For example, although medical gauze and hemostatic bandages can temporarily control bleeding, gauze stops bleeding by compressing the blood vessels of the wound, which may lead to excessive blood absorption and increase the risk of blood loss; although hemostatic bandages can block blood flow, long-term use may cause serious damage to surrounding tissues and even lead to limb necrosis; commercial hemostatic powders only have the function of absorbing blood and cannot tightly seal the wound, increasing the risk of heavy bleeding. Gel has become an ideal hemostatic material due to its excellent biocompatibility, sufficient mechanical strength, strong water absorption capacity and versatility. Self-gel hemostatic powder is a material made by freeze-drying gel and then finely grinding it. It combines the advantages of gel and powder materials, can quickly absorb blood into gel, and fits bleeding wounds of various depths and shapes to form a firm seal.
[0003] The present invention first obtains a urea-modified (meth) acrylic acid monomer by reacting (meth) acrylate isocyanoethyl with glycine, then grafts chitosan with 2,3-epoxypropyltrimethylammonium chloride to obtain quaternized chitosan, blends the urea-modified (meth) acrylic acid monomer with quaternized chitosan or ε-polylysine, and finally prepares a gel by a free radical-initiated double bond polymerization reaction. After freeze-drying and grinding the gel, a self-gelling hemostatic powder can be obtained, which can achieve rapid gelation and rapid hemostasis by virtue of multiple non-covalent effects. The self-gelling hemostatic powder exhibits excellent adhesion properties, antibacterial properties, and the effects of promoting wound healing and rapid hemostasis. This makes the self-gelling hemostatic powder have potential application prospects in biological fields such as wound dressings and medical hemostasis. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a self-gelling hemostatic powder based on multiple non-covalent interactions, which replaces the cross-linking effect of a small molecule cross-linking agent by the force of hydrogen bonds between polymer molecules and the electrostatic interaction of positive and negative charges between amino and carboxyl groups, so that the gel can be gelled without adding any cross-linking agent, and the self-gelling hemostatic powder obtained after freeze-drying and grinding the gel exhibits excellent adhesion properties, antibacterial properties, and promotes wound healing and rapid hemostasis. The self-gelling hemostatic powder overcomes the adhesion limitations of traditional hemostatic powder materials and can achieve rapid and effective hemostasis for irregularly shaped, non-pressible internal organs and high-pressure arterial bleeding.
[0005] The technical purpose of the present invention is achieved through the following technical solutions.
[0006] A method for preparing a self-gelling hemostatic powder based on multiple non-covalent interactions, characterized in that a urea-modified (meth) acrylic acid monomer is dissolved in water, dimethyl sulfoxide or a mixed solution of the two to prepare a solution with a molar concentration of 1 to 7 mol / L, and then 0 to 20% of quaternized chitosan or ε-polylysine is added, and then a photoinitiator or thermal initiator equivalent to 0.1-2% of the mass fraction of the urea-modified (meth) acrylic acid monomer is added, and after mixing, the mixture is deoxygenated and injected into a closed mold, and the monomer polymerization is initiated by photoinitiation or thermal initiation. After a certain reaction time, the prepared gel is demoulded and soaked in water for at least 1 day to remove unreacted monomers, and then the gel is freeze-dried and ground to obtain a self-gelling hemostatic powder.
[0007] The above-mentioned selection of 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173) or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) or phenyl (2,4,6-trimethylbenzoyl) lithium phosphite (photoinitiator LAP) or ammonium persulfate as a photoinitiator or thermal initiator.
[0008] When 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173) or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) is selected as the initiator for crosslinking, it is placed in an ultraviolet light crosslinker to initiate monomer polymerization, and the reaction time is 10 to 180 minutes. When phenyl (2,4,6-trimethylbenzoyl) lithium phosphinate (photoinitiator LAP) is selected as the photoinitiator, it is placed in a blue light crosslinker to initiate monomer polymerization, and the reaction time is 10 to 180 minutes. When ammonium persulfate is selected as the thermal initiator, it is placed in an oven for heating to initiate monomer polymerization, the polymerization reaction temperature is 60-80° C., and the polymerization time is 12 hours.
[0009] The synthesis method of the urea-modified (meth) acrylic acid monomer is as follows:
[0010] Isocyanoethyl (meth)acrylate and glycine containing an amino group are reacted to generate a urea-modified (meth)acrylic acid monomer. First, glycine and sodium hydroxide are dissolved in water at a molar ratio of 1: (1-1.5), and mixed and reacted at low temperature (0-10°C) for 15-45 minutes to obtain a sodium glycine aqueous solution; then, isocyanoethyl (meth)acrylate is dissolved in tetrahydrofuran according to 1-1.5 equivalents of glycine, and then added to the sodium glycine aqueous solution, and the reaction is continued for 1-6 hours at room temperature; the solution after the reaction is extracted with ethyl acetate, and the pH value of the aqueous solution obtained by the extraction is adjusted to 1-3 with hydrochloric acid to obtain an acidic aqueous solution; then, the acidic aqueous solution is extracted with ethyl acetate, and the ethyl acetate solution obtained by the extraction is dried with anhydrous magnesium sulfate and filtered, and then the filtered solution is precipitated in n-hexane to obtain a white precipitate, and dried in a vacuum drying oven to obtain a urea-modified (meth)acrylic acid monomer. Its structural formula is as follows:
[0011]
[0012] Wherein, R is CH3 or H.
[0013] The above-mentioned quaternized chitosan synthesis method is as follows:
[0014] Chitosan with a mass concentration of 1 to 6% is dissolved in an acetic acid aqueous solution with a mass concentration of 0.5 to 1%, and the mixture is continuously stirred and dissolved at 45 to 60° C. for 30 to 60 minutes. According to the molar ratio of amino groups on chitosan to 2,3-epoxypropyltrimethylammonium chloride of 1:(1 to 5), 2,3-epoxypropyltrimethylammonium chloride is weighed and added to react with chitosan. After reacting for 15 to 18 hours under stirring at 45 to 60° C., the product is centrifuged at room temperature, the supernatant is taken and precipitated with acetone to obtain a solid crude product, and then the crude product is dried in a vacuum drying oven to obtain quaternized chitosan. The structural formula of the quaternized chitosan is as follows:
[0015]
[0016] Where R is Or H; m is the degree of polymerization of quaternized chitosan, which is 600-2000.
[0017] The structural formula of the ε-polylysine is shown below:
[0018]
[0019] Wherein n is the degree of polymerization of ε-polylysine, and its value is 10-100.
[0020] Compared with the prior art, the present invention first generates a urea-modified (meth)acrylic acid monomer by reacting (meth)acrylic acid isocyanoethyl and amino-containing glycine, and then synthesizes quaternized chitosan by reacting chitosan with 2,3-epoxypropyltrimethylammonium chloride. The urea-modified (meth)acrylic acid monomer is further blended with quaternized chitosan or ε-polylysine, and then a gel is prepared by free radical polymerization without adding any cross-linking agent. The gel is freeze-dried and ground to obtain a self-gelling hemostatic powder, which has excellent cohesive energy and adhesion properties due to multiple non-covalent interactions and can achieve rapid gelation. This makes the self-gelling hemostatic powder have potential application prospects in biological fields such as antibacterial, wound healing, and rapid hemostasis.
[0021] The advantages of the present invention are: (1) the raw materials are easily available, and the synthesis and preparation methods are simple; (2) the self-gelling hemostatic powder can quickly form a gel in a liquid environment by cross-linking with multiple non-covalent interactions, thereby achieving rapid hemostasis; (3) the self-gelling hemostatic powder has good antibacterial properties and can promote wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The figure is the nuclear magnetic spectrum of the urea-modified methacrylic acid monomer prepared by the present invention.
[0023] Figure 2 The figure is the nuclear magnetic spectrum of the quaternized chitosan prepared by the present invention.
[0024] Figure 3 The figure is the nuclear magnetic spectrum of the urea-modified acrylic acid monomer prepared by the present invention.
[0025] Figure 4 The self-gel hemostatic powder prepared by the invention is added with water to form a gel.
[0026] Figure 5 The present invention is a shear tensile strength curve of the self-gel hemostatic powder prepared by the present invention adhering to pig skin tissue after adding water.
[0027] Figure 6 The stress-strain curve diagram of the self-gelling hemostatic powder prepared by the present invention after being gelled with water.
[0028] Figure 7 The invention discloses the hemostatic effect of the self-gelling hemostatic powder prepared by the invention in a rat liver hemorrhage model. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the scope of the present invention is not limited thereto.
[0030] The nuclear magnetic resonance spectrometer was used to perform the nuclear magnetic hydrogen spectrum test, and deuterated water was used as the solvent. The test was carried out at room temperature, and the nuclear magnetic hydrogen spectrum proved that all monomers were successfully synthesized. The universal pressure tester was used to test the adhesion properties of the prepared self-gel hemostatic powder to pig skin tissue and the mechanical properties after adding water to form gel. The rat liver bleeding model was used to test the hemostatic effect of the self-gel hemostatic powder.
[0031] Example 1
[0032] (1) The preparation method of urea-modified methacrylic acid monomer is as follows:
[0033] Glycine (5.00 g) and sodium hydroxide (2.67 g) were weighed and dissolved in 40 mL ultrapure water in a molar ratio of 1:1, and reacted at low temperature for 15 minutes to obtain a sodium glycine aqueous solution; then 1 equivalent of glycine (10.33 g) of isocyanoethyl methacrylate was weighed and dissolved in 5 mL of tetrahydrofuran, and then added to the sodium glycine aqueous solution, and the reaction was continued for 1 hour at room temperature; the solution after the reaction was extracted with ethyl acetate, and the pH value of the aqueous solution obtained by the extraction was adjusted to 1 with hydrochloric acid to obtain an acidic aqueous solution; then the acidic aqueous solution was extracted with ethyl acetate, and the ethyl acetate solution obtained by the extraction was dried with anhydrous magnesium sulfate and filtered, and then the filtered solution was precipitated in n-hexane to obtain a white precipitate, and dried in a vacuum drying oven to obtain a urea-modified (meth) acrylic acid monomer. Its structural formula is as follows:
[0034]
[0035] The H NMR spectrum is attached. Figure 1 As shown, it is proved that the urea-modified methacrylic acid monomer was successfully synthesized.
[0036] (2) The preparation method of quaternized chitosan is as follows:
[0037] Chitosan (0.30 g) with a mass concentration of 1% was added to 30 mL of ultrapure water, and then glacial acetic acid (143 μL) with a mass concentration of 0.5% was added to the suspension and stirred and dissolved at 45°C for 30 minutes. According to the molar ratio of the amino group on the chitosan to 2,3-epoxypropyltrimethylammonium chloride of 1:1, 2,3-epoxypropyltrimethylammonium chloride (0.24 g) was weighed and added to react with the chitosan. After reacting for 15 hours at 45°C, the product was centrifuged at room temperature, and the supernatant was taken and precipitated with acetone to obtain a solid crude product, and then the crude product was dried in a vacuum drying oven to obtain quaternized chitosan. Its structural formula is as follows:
[0038]
[0039] Where R is Or H; m is the degree of polymerization of quaternized chitosan, which is 600.
[0040] The H NMR spectrum is attached. Figure 2 As shown, it proves that quaternary ammonium chitosan was successfully synthesized.
[0041] (3) The preparation method of self-gel hemostatic powder is as follows:
[0042] The prepared urea-modified methacrylic acid monomer is weighed and dissolved in ultrapure water to prepare a solution with a molar concentration of 3 mol / L. Quaternized chitosan with a mass concentration of 3% is weighed and added to the above solution, and then a 1173 photoinitiator with a mass concentration of 0.1% of the urea-modified methacrylic acid monomer is added, and the mixture is cured under ultraviolet light for 30 minutes, and then demolded to obtain a gel, and the gel is soaked in ultrapure water for 3 days to reach swelling equilibrium, and the gel after swelling equilibrium is freeze-dried and ground to obtain a self-gelling hemostatic powder.
[0043] As attached Figure 4 As shown in the figure, after adding water, the self-gelling hemostatic powder can form a gel and can be picked up with tweezers. The adhesion strength of the self-gelling hemostatic powder when it adheres to two pieces of pig skin was further tested using a universal testing machine. The amount of powder added was 40 mg and the adhesion area was 1 cm 2 , add 80 μL of water, as shown in the attached Figure 5 As shown in the figure, the shear adhesion strength of the self-gelling hemostatic powder can reach 55 kPa, which is due to the hydrogen bonding and electrostatic interaction between the self-gelling hemostatic powder and the pig skin tissue, which makes the two pieces of pig skin tightly adhere together. The compression resistance of the self-gelling hemostatic powder was further tested by adding water to the self-gelling hemostatic powder in a cylindrical mold according to a solid content of 33 wt%. Figure 6 As shown in the figure, the compressive fracture stress of the self-gelling hemostatic powder at 90% strain after gelation can also reach 3.9MPa. The hemostatic effect of the self-gelling hemostatic powder was tested by a rat liver bleeding model, as shown in the attached figure. Figure 7 As shown, compared with the blank control group, the rat liver treated with the self-gelling hemostatic powder had a significant hemostatic effect and significantly reduced the amount of bleeding. The control group lost 725 mg of blood, while the self-gelling hemostatic powder lost only 52 mg of blood.
[0044] Example 2
[0045] (1) The preparation method of urea-modified acrylic monomer is as follows:
[0046] Glycine (5.00 g) and sodium hydroxide (3.46 g) were weighed and dissolved in 40 mL ultrapure water at a molar ratio of 1:1.3, and reacted at low temperature for 30 minutes to obtain a sodium glycine aqueous solution; 1.3 equivalents (12.22 g) of acrylate was weighed and dissolved in 5 mL of tetrahydrofuran, and then added to the sodium glycine aqueous solution, and the reaction was continued for 3 hours at room temperature; the solution after the reaction was extracted with ethyl acetate, and the pH value of the aqueous solution obtained by the extraction was adjusted to 2 with hydrochloric acid to obtain an acidic aqueous solution; the acidic aqueous solution was then extracted with ethyl acetate, and the ethyl acetate solution obtained by the extraction was dried with anhydrous magnesium sulfate and filtered, and the filtered solution was precipitated in n-hexane to obtain a white precipitate, and dried in a vacuum drying oven to obtain a urea-modified acrylic monomer. Its structural formula is as follows:
[0047]
[0048] The H NMR spectrum is attached. Figure 3 As shown, it is proved that the urea-modified acrylic monomer was successfully synthesized.
[0049] (2) The preparation method of quaternized chitosan is as follows:
[0050] Chitosan (0.90 g) with a mass concentration of 3% was added to 30 mL of ultrapure water, and then glacial acetic acid (229 μL) with a mass concentration of 0.8% was added to the suspension and stirred and dissolved at 55°C for 30 minutes. According to the feeding ratio of 1:3 between the amino group on the chitosan and 2,3-epoxypropyltrimethylammonium chloride, 2,3-epoxypropyltrimethylammonium chloride (1.33 g) was weighed and added to react with chitosan. After stirring at 50°C for 16 hours, the product was centrifuged at room temperature, the supernatant was taken and precipitated with acetone to obtain a solid crude product, and then the crude product was dried in a vacuum drying oven to obtain quaternized chitosan. Its structural formula is as follows:
[0051]
[0052] Where R is Or H; m is the degree of polymerization of quaternized chitosan, which is 1200.
[0053] (3) The preparation method of self-gel hemostatic powder is as follows:
[0054] The prepared urea-modified acrylic monomer is weighed and dissolved in a solution of equal volumes of ultrapure water and dimethyl sulfoxide to prepare a solution with a molar concentration of 4 mol / L. Quaternary ammonium chitosan with a mass concentration of 4% is weighed and added to the above solution, and then a 2959 photoinitiator with a mass concentration of 0.5% of the urea-modified acrylic monomer is added, and the mixture is cured under ultraviolet light for 40 minutes, and then demolded to obtain a gel, and the gel is soaked in ultrapure water for 3 days to reach swelling equilibrium, and the gel after swelling equilibrium is freeze-dried and ground to obtain a self-gelling hemostatic powder.
[0055] The adhesion strength of the self-gelling hemostatic powder on two pieces of pig skin was further tested using a universal testing machine. The amount of powder added was 40 mg and the adhesion area was 1 cm 2 , the amount of water added is 80μL, the shear adhesion strength of the self-gelling hemostatic powder can reach 50kPa, which is due to the hydrogen bonding and electrostatic interaction between the self-gelling hemostatic powder and the pig skin tissue, which makes it tightly adhere the two pieces of pig skin together. After the self-gelling hemostatic powder is gelled in a cylindrical mold with a solid content of 50wt%, the compression resistance of the self-gelling hemostatic powder is further tested. After the self-gelling hemostatic powder is gelled, the compressive fracture stress at 90% strain can also reach 2.5MPa. The hemostatic effect of the self-gelling hemostatic powder was tested by the rat liver bleeding model. Compared with the blank control group, the rat liver with the self-gelling hemostatic powder had a significant hemostatic effect and significantly reduced the amount of bleeding. The blood loss of the control group was 825mg, and the blood loss of the self-gelling hemostatic powder was only 65mg.
[0056] Example 3
[0057] (1) The preparation method of urea-modified methacrylic acid monomer is as follows:
[0058] Glycine (5.00 g) and sodium hydroxide (3.73 g) were weighed and dissolved in 40 mL ultrapure water at a molar ratio of 1:1.4, and reacted at low temperature for 40 minutes to obtain a sodium glycine aqueous solution; then 1.4 equivalents (14.47 g) of glycine was weighed and dissolved in 5 mL of tetrahydrofuran, mixed and then added to the sodium glycine aqueous solution, and the room temperature was restored to continue the reaction for 4 hours; the solution after the reaction was extracted with ethyl acetate, and the pH value of the aqueous solution obtained by the extraction was adjusted to 2.5 with hydrochloric acid to obtain an acidic aqueous solution; then the acidic aqueous solution was extracted with ethyl acetate, and the ethyl acetate solution obtained by the extraction was dried with anhydrous magnesium sulfate and filtered, and then the filtered solution was precipitated in n-hexane to obtain a white precipitate, and dried in a vacuum drying oven to obtain a urea-modified methacrylic acid monomer. Its structural formula is as follows:
[0059]
[0060] The H NMR spectrum is attached. Figure 1 As shown, it is proved that the urea-modified methacrylic acid monomer was successfully synthesized.
[0061] (2) The structural formula of ε-polylysine is as follows:
[0062]
[0063] Wherein n is the degree of polymerization of ε-polylysine, and its value is 10-100.
[0064] (3) The preparation method of self-gel hemostatic powder is as follows:
[0065] The prepared urea-modified methacrylic acid monomer is weighed and dissolved in a solution of equal volumes of ultrapure water and dimethyl sulfoxide to prepare a solution with a molar concentration of 6 mol / L. 10% ε-polylysine is weighed and added to the above solution, and then ammonium persulfate with a mass concentration of 1% of the urea-modified methacrylic acid monomer is added as a thermal initiator, and cured at 60° C. for 12 hours, and then demolded to obtain a gel, which is soaked in ultrapure water for 3 days to reach swelling equilibrium, and the gel after swelling equilibrium is freeze-dried and ground to obtain a self-gelling hemostatic powder.
[0066] The adhesion strength of the self-gelling hemostatic powder on two pieces of pig skin was further tested using a universal testing machine. The amount of powder added was 40 mg and the adhesion area was 1 cm 2 , the amount of water added was 80μL, and the shear adhesion strength of the self-gelling hemostatic powder could reach 45kPa, which was due to the hydrogen bonding and electrostatic interaction between the self-gelling hemostatic powder and the pig skin tissue, which made it tightly adhere the two pieces of pig skin together. After the self-gelling hemostatic powder was gelled in a cylindrical mold with a solid content of 60wt%, the compression resistance of the self-gelling hemostatic powder was further tested. After the self-gelling hemostatic powder was gelled, the compressive fracture stress at 90% strain could also reach 2.8MPa. The hemostatic effect of the self-gelling hemostatic powder was tested by the rat liver bleeding model. Compared with the blank control group, the rat liver with the self-gelling hemostatic powder had a significant hemostatic effect and significantly reduced the amount of bleeding. The blood loss of the control group was 736mg, and the blood loss of the self-gelling hemostatic powder was only 45mg.
[0067] Example 4
[0068] (1) The preparation method of urea-modified methacrylic acid monomer is as follows:
[0069] Glycine (5.00 g) and sodium hydroxide (4 g) were weighed and dissolved in 40 mL ultrapure water at a molar ratio of 1:1.5, and reacted at low temperature for 45 minutes to obtain a sodium glycine aqueous solution; then 1.5 equivalents (15.50 g) of glycine was weighed and dissolved in 5 mL of tetrahydrofuran, and then added to the sodium glycine aqueous solution, and the reaction was continued for 6 hours at room temperature; the solution after the reaction was extracted with ethyl acetate, and the pH value of the aqueous solution obtained by the extraction was adjusted to 3 with hydrochloric acid to obtain an acidic aqueous solution; then the acidic aqueous solution was extracted with ethyl acetate, and the ethyl acetate solution obtained by the extraction was dried with anhydrous magnesium sulfate and filtered, and then the filtered solution was precipitated in n-hexane to obtain a white precipitate, and dried in a vacuum drying oven to obtain a urea-modified methacrylic acid monomer. Its structural formula is as follows:
[0070]
[0071] The H NMR spectrum is attached. Figure 1 As shown, it is proved that the urea-modified methacrylic acid monomer was successfully synthesized.
[0072] (2) The preparation method of quaternized chitosan (QCS) is as follows:
[0073] Chitosan (1.8 g) with a mass concentration of 6% was added to 30 mL of ultrapure water, and then glacial acetic acid (286 μL) with a mass concentration of 1% was added to the suspension and stirred and dissolved at 60°C for 60 minutes. According to the molar ratio of amino groups on chitosan to 2,3-epoxypropyltrimethylammonium chloride of 1:5, 2,3-epoxypropyltrimethylammonium chloride (7.20 g) was added to react with chitosan. After stirring at 60°C for 18 hours, the product was centrifuged at room temperature, the supernatant was taken and precipitated with acetone to obtain a solid crude product, and then the crude product was dried in a vacuum drying oven to obtain quaternized chitosan. Its structural formula is as follows:
[0074]
[0075] Where R is Or H; m is the degree of polymerization of quaternized chitosan, which is 2000.
[0076] The H NMR spectrum is attached. Figure 2 As shown, it proves that quaternary ammonium chitosan was successfully synthesized.
[0077] (3) The preparation method of self-gel hemostatic powder is as follows:
[0078] The prepared urea-modified methacrylic acid monomer is weighed and dissolved in dimethyl sulfoxide to prepare a solution with a molar concentration of 6 mol / L. Quaternized chitosan with a mass concentration of 6% is weighed and added to the above solution, and then a (2,4,6-trimethylbenzoyl) lithium phosphinate photoinitiator with a mass concentration of 2% of the urea-modified methacrylic acid monomer is added, and the mixture is cured under blue light for 60 minutes, and then demolded to obtain a gel, and the gel is soaked in ultrapure water for 3 days to reach swelling equilibrium, and the gel after swelling equilibrium is freeze-dried and ground to obtain a self-gelling hemostatic powder.
[0079] The adhesion strength of the self-gelling hemostatic powder on two pieces of pig skin was further tested using a universal testing machine. The amount of powder added was 40 mg and the adhesion area was 1 cm 2 , the amount of water added was 80μL, and the shear adhesion strength of the self-gelling hemostatic powder could reach 45kPa, which was due to the hydrogen bonding and electrostatic interaction between the self-gelling hemostatic powder and the pig skin tissue, which made it tightly adhere the two pieces of pig skin together. After the self-gelling hemostatic powder was gelled in a cylindrical mold with a solid content of 66wt%, the compression resistance of the self-gelling hemostatic powder was further tested. After the self-gelling hemostatic powder was gelled, the compressive fracture stress at 90% strain could reach 4.2MPa. The hemostatic effect of the self-gelling hemostatic powder was tested by the rat liver bleeding model. Compared with the blank control group, the rat liver with the self-gelling hemostatic powder had a significant hemostatic effect and significantly reduced the amount of bleeding. The blood loss of the control group was 846mg, and the blood loss of the self-gelling hemostatic powder was only 49mg.
[0080] According to the content of the present invention, the process parameters can be adjusted to achieve the preparation of self-gelling hemostatic powder, which shows basically the same performance as the present invention after testing. The above is an exemplary description of the present invention. Without departing from the core of the present invention, any simple deformation, modification or equivalent replacement that can be made by other technicians in this field without spending creative labor falls within the protection scope of the present invention.
Claims
1. A method for preparing a self-gelling hemostatic powder based on multiple non-covalent interactions, characterized in that: The urea-modified (meth) acrylic acid monomer is dissolved in water, dimethyl sulfoxide or a mixed solution of the two to prepare a solution with a molar concentration of 1-7 mol / L, and then quaternized chitosan or ε-polylysine with a mass volume fraction of 0-20% is added, and then a photoinitiator or a thermal initiator equivalent to 0.1-2% of the mass fraction of the urea-modified (meth) acrylic acid monomer is added, and after mixing, oxygen is removed and injected into a closed mold, and monomer polymerization is initiated by photoinitiation or thermal initiation. After a certain reaction time, the prepared gel is demoulded and immersed in water for at least 1 day to remove unreacted monomers, and then the gel is freeze-dried and ground to obtain a self-gel hemostatic powder. The structure of the urea-modified (meth) acrylic acid monomer is shown below: Wherein, R is CH3 or H. The structural formula of the quaternized chitosan is as follows: Where R is Or H; m is the degree of polymerization of quaternized chitosan, which is 600-2000. The structural formula of the ε-polylysine is shown below: Wherein n is the degree of polymerization of ε-polylysine, and its value is 10-100.
2. According to claim 1, a method for preparing a self-gelling hemostatic powder based on multiple non-covalent interactions, characterized in that: The initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173) or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) or lithium phenyl (2,4,6-trimethylbenzoyl) phosphinate (photoinitiator LAP) or ammonium persulfate as a photoinitiator or thermal initiator.
3. According to claim 1, a method for preparing a self-gelling hemostatic powder based on multiple non-covalent interactions, characterized in that: When 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173) or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) is selected as the initiator for crosslinking, it is placed in an ultraviolet light crosslinker to initiate monomer polymerization, and the reaction time is 10 to 180 minutes. When phenyl (2,4,6-trimethylbenzoyl) lithium phosphinate (photoinitiator LAP) is selected as the photoinitiator, it is placed in a blue light crosslinker to initiate monomer polymerization, and the reaction time is 10 to 180 minutes. When ammonium persulfate is selected as the thermal initiator, it is placed in an oven for heating to initiate monomer polymerization, the polymerization reaction temperature is 60-80° C., and the polymerization time is 12 hours.
4. According to claim 1, a method for preparing a self-gelling hemostatic powder based on multiple non-covalent interactions, characterized in that: The synthesis method of urea-modified (meth) acrylic acid monomer is as follows: Isocyanoethyl (meth)acrylate and glycine containing an amino group are reacted to generate a urea-modified (meth)acrylic acid monomer. First, glycine and sodium hydroxide are dissolved in water at a molar ratio of 1: (1-1.5), and mixed and reacted at low temperature (0-10°C) for 15-45 minutes to obtain a sodium glycine aqueous solution; then, isocyanoethyl (meth)acrylate is dissolved in tetrahydrofuran according to 1-1.5 equivalents of glycine, and then added to the sodium glycine aqueous solution, and the reaction is continued for 1-6 hours at room temperature; the solution after the reaction is extracted with ethyl acetate, and the pH value of the aqueous solution obtained by the extraction is adjusted to 1-3 with hydrochloric acid to obtain an acidic aqueous solution; then, the acidic aqueous solution is extracted with ethyl acetate, and the ethyl acetate solution obtained by the extraction is dried with anhydrous magnesium sulfate and filtered, and then the filtered solution is precipitated in n-hexane to obtain a white precipitate, and dried in a vacuum drying oven to obtain a urea-modified (meth)acrylic acid monomer. Its structural formula is as follows: Wherein, R is CH3 or H.
5. According to claim 1, a method for preparing a self-gelling hemostatic powder based on multiple non-covalent interactions, characterized in that: The synthesis method of quaternized chitosan is as follows: Chitosan with a mass concentration of 1-6% is dissolved in an acetic acid aqueous solution with a mass concentration of 0.5-1%, and the mixture is continuously stirred and dissolved at 45-60°C for 30-60 minutes. According to the molar ratio of amino groups on chitosan to 2,3-epoxypropyltrimethylammonium chloride of 1:(1-5), 2,3-epoxypropyltrimethylammonium chloride is weighed and added to react with chitosan. After reacting for 15-18 hours under stirring at 45-60°C, the product is centrifuged at room temperature, the supernatant is taken and precipitated with acetone to obtain a solid crude product, and then the crude product is dried in a vacuum drying oven to obtain quaternized chitosan. Its structure is shown below: Where R is Or H; m is the degree of polymerization of quaternized chitosan, which is 600-2000.
6. According to claim 1, a method for preparing a self-gelling hemostatic powder based on multiple non-covalent interactions, characterized in that: The solvent used for preparing the hydrogel is water, dimethyl sulfoxide or a mixed solvent thereof.
Citation Information
Patent Citations
Preparation method of styptic powder
CN106178088A
Antibacterial, repair-promoting, hemostatic and anti-adhesion membrane and preparation method thereof
CN112007200A
Hydrogel powder for rapid hemostasis and preparation method and application thereof
CN114767919A
Quick-water-absorption self-gel antibacterial hemostatic powder as well as preparation method and application thereof
CN116036351A
High-strength self-healing amido urea zwitterionic hydrogel and preparation method thereof
CN116375918A